2016
DOI: 10.1111/dom.12632
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of liraglutide 3.0 mg for weight management are similar across races: subgroup analysis across the SCALE and phase II randomized trials

Abstract: The efficacy and safety of liraglutide 3.0 mg versus placebo, as adjunct to diet and exercise, was evaluated in racial subgroups. This post hoc analysis of pooled data from five double‐blind randomized, placebo‐controlled trials was conducted in 5325 adults with either a body mass index (BMI) ≥27 kg/m2 plus ≥1 comorbidity or a BMI ≥30 kg/m2. Statistical interaction tests evaluated possible treatment effect differences between racial subgroups: white (4496, 84.4%), black/African‐American (550, 10.3%), Asian (16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 14 publications
3
19
0
3
Order By: Relevance
“…Liraglutide‐treated participants also had significantly greater increases than IBT‐alone on the SF‐36 MCS score. The present results confirm previous reports that liraglutide, compared with placebo (both combined with lifestyle counselling), improves both HRQoL and weight‐related QoL …”
Section: Discussionsupporting
confidence: 77%
“…Liraglutide‐treated participants also had significantly greater increases than IBT‐alone on the SF‐36 MCS score. The present results confirm previous reports that liraglutide, compared with placebo (both combined with lifestyle counselling), improves both HRQoL and weight‐related QoL …”
Section: Discussionsupporting
confidence: 77%
“…This pilot study found that modest (~4%) weight loss induced with liraglutide 3 mg daily for 26 weeks was as effective as a combined diet and exercise for reducing transaminase, liver fat and stiffness levels in obese Asian adults with NAFLD. As far as we know, this is the first randomized trial comparing the effects on NAFLD of weight loss induced with liraglutide at the highest approved dose of 3 mg daily vs a structured lifestyle modification. In previous studies, liraglutide at lower doses (≤1.8 mg daily) reduced liver fat and transaminase levels.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we are aware, there are no published comparisons of the effects on NAFLD of a structured weight‐loss lifestyle intervention with liraglutide. In this pilot randomized study we therefore compared 26 weeks of once‐daily injection of liraglutide at the 3 mg dose approved for weight loss with a supervised program of energy restriction plus exercise designed to induce 7% weight loss, in obese Asian adults with NAFLD. The main outcomes were the changes in weight, liver fat and serum transaminase levels.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative efficacy of liraglutide was evaluated above and below a BMI of 35kg/m 2 and found that liraglutide performed equally well in both classes of obesity[99]. Efficacy of liraglutide was compared across racial groups and was shown to give similar weight loss[100]. Due to the concern about neuropsychiatric symptoms from a centrally acting obesity medication, these symptoms were evaluated with validated questionnaires and there was no significant difference detected between the liraglutide and placebo groups in depression, anxiety, suicidal ideation or suicidal behavior[101].…”
Section: Current Centrally Acting Anti-obesity Drugsmentioning
confidence: 99%